Safety profile of the RTS, S/AS01 malaria vaccine in infants and children: additional data from a phase III randomized controlled trial in sub-Saharan Africa. Issue 10 (3rd October 2019) - Guerra Mendoza, Yolanda; Garric, Elodie; Leach, Amanda; Lievens, Marc; Ofori-Anyinam, Opokua; Pirçon, Jean-Yves; Stegmann, Jens-Ulrich; Vandoolaeghe, Pascale; Otieno, Lucas; Otieno, Walter; Owusu-Agyei, Seth; Sacarlal, Jahit; et al.
ABSTRACT: A phase III, double-blind, randomized, controlled trial (NCT00866619) in sub-Saharan Africa showed RTS, S/AS01 vaccine efficacy against malaria. We now present in-depth safety results from this study. 8922 children (enrolled at 5–17 months) and 6537 infants (enrolled at 6–12 weeks) were 1:1:1-randomized to receive 4 doses of RTS, S/AS01 (R3R) or non-malaria control vaccine (C3C), or 3 RTS, S/AS01 doses plus control (R3C). Aggregate safety data were reviewed by a multi-functional team. Severe malaria with Blantyre Coma Score ≤2 (cerebral malaria [CM]) and gender-specific mortality were assessed post-hoc . Serious adverse event (SAE) and fatal SAE incidences throughout the study were 24.2%–28.4% and 1.5%–2.5%, respectively across groups; 0.0%–0.3% of participants reported vaccination-related SAEs. The incidence of febrile convulsions in children was higher during the first 2–3 days post-vaccination with RTS, S/AS01 than with control vaccine, consistent with the time window of post-vaccination febrile reactions in this study (mostly the day after vaccination). A statistically significant numerical imbalance was observed for meningitis cases in children (R3R: 11, R3C: 10, C3C: 1) but not in infants. CM cases were more frequent in RTS, S/AS01-vaccinated children (R3R: 19, R3C: 24, C3C: 10) but not in infants. All-cause mortality was higher in RTS, S/AS01-vaccinated versus control girls (2.4% vs 1.3%, all ages) in our setting with low overall mortality. The observed meningitis and CM signals are considered likely chance findings, that – given their severity – warrant further evaluation in phase IV studies and WHO-led pilot implementation programs to establish the RTS, S/AS01 benefit-risk profile in real-life settings.